Institutional pressures, isomorphic changes and key agents in the transfer of knowledge of Lean in Healthcare. Issue 1 (14th August 2018) - D'Andreamatteo, Antonio; Ianni, Luca; Rangone, Adalberto; Paolone, Francesco; Sargiacomo, Massimo
Abstract : Purpose: Application of operations management in healthcare is particularly promising to improve the overall organisational performance, although the Italian system is behind in introducing related techniques and methods. One of the recent experiments in healthcare is the implementation of "Lean Thinking". The purpose of this paper is to investigate which exogenous forces are driving knowledge transfer on Lean, both in the private and public healthcare sectors. Design/methodology/approach: Informed by institutional sociology (DiMaggio and Powell, 1983 ; Powell and DiMaggio, 1991 ), the paper builds on the case study methodology (Yin, 2013 ) to elucidate the environmental pressures that are encouraging the adoption of Lean thinking by Italian hospitals and Local Health Authorities. Findings: The study highlights the economic, coercive, mimetic and normative pressures that are triggering the adoption of Lean thinking in the Italian National Health System (INHS). At the same time, the authors reveal the pivotal importance and innovative roles played by diverse prominent key-actors in the different organisations investigated. Originality/value: Considering that little is known to date regarding which exogenous forces are driving the transfer of knowledge on Lean, especially in the public healthcare sector, the paper allows scholars to focus on patterns of isomorphic change and will facilitate managers and policy makers to understand exogenous factors stimulating the transfer of Lean thinking and the subsequent innovation within health organisations and systems.